A thermodynamic assessment of the binary Fe-Mn system for the third generation of Calphad databases. (March 2019) - Bigdeli, Sedigheh; Selleby, Malin
Abstract: In developing the third generation of Calphad databases, the next step after proper description of the unaries is to assess higher-order systems, i.e. binaries, ternaries etc. A new description of the Fe-Mn system is presented in this work, based on the Calphad approach. New models with a stronger physical basis are used to model the Gibbs energy of the phases. For this purpose, the revised magnetic model is used to fit the magnetic properties versus the most recent experimental and ab-initio data. An acceptable magnetic phase diagram is reproduced, and a reasonable fit for the phase diagram is achieved which will prevent possible artefacts in higher-order systems. The description is valid down to 0 K, which make it very useful as a starting point for modelling phase transformations occurring at low temperatures.